Braving the extremes: foraminifera document changes in climate-induced and anthropogenic stress in Wadden Sea salt marshes - Bunzel, Dorothea; Milker, Yvonne; Francescangeli, Fabio; Schmiedl, Gerhard (Frontiers in Ecology and Evolution, 2023)
Tidal wetlands are highly dynamic ecosystems that are susceptible to changes in sea level and flooding from storm surges. Among them, salt marshes play a key role in coastal protection as they contribute to wave attenuation through their regulating ecosystem services, thereby promoting sediment deposition and shoreline stabilization. However, the resilience of salt marshes, particularly those that have been modified and cultivated for centuries, is questionable in the face of accelerated sea level rise (SLR) and increasing run-up heights of storm surges. In this context, this study aims to investigate the historical foraminiferal records of two sedimentary salt marsh archives from the Wadden Sea area (Dithmarschen and North Frisia, Germany) that have been modified to varying degrees by human management activities over the last century. The foraminiferal records document how physico-chemical traits of salt marshes of the central Wadden Sea have responded to storm tide inundation over the last century, providing information about salt marsh stability and vulnerability. Abnormally grown tests of the salt marsh indicator species Entzia macrescens increased in number between 1950 CE and the late 1980s, indicating the concurrent increase of environmental stress caused by the effects of times of increased salt marsh flooding. These trends can be linked to observations of amplified North Sea storm surges, corroborating that salt-marsh ecosystems respond to changing climate conditions. Differences in the number of abnormal foraminifera between the studied salt marshes suggest a particularly high vulnerability of intensively human-modified coastal wetland ecosystems to amplified storm climate conditions.